Dislocation‐Free and Atomically Flat GaN Hexagonal Microprisms for Device Applications. Issue 30 (24th June 2020) - Khalilian, Maryam; Bi, Zhaoxia; Johansson, Jonas; Lenrick, Filip; Hultin, Olof; Colvin, Jovana; Timm, Rainer; Wallenberg, Reine; Ohlsson, Jonas; Pistol, Mats‐Erik; Gustafsson, Anders; Samuelson, Lars
Abstract: III‐nitrides are considered the material of choice for light‐emitting diodes (LEDs) and lasers in the visible to ultraviolet spectral range. The development is hampered by lattice and thermal mismatch between the nitride layers and the growth substrate leading to high dislocation densities. In order to overcome the issue, efforts have gone into selected area growth of nanowires (NWs), using their small footprint in the substrate to grow virtually dislocation‐free material. Their geometry is defined by six tall side‐facets and a pointed tip which limits the design of optoelectronic devices. Growth of dislocation‐free and atomically smooth 3D hexagonal GaN micro‐prisms with a flat, micrometer‐sized top‐surface is presented. These self‐forming structures are suitable for optical devices such as low‐loss optical cavities for high‐efficiency LEDs. The structures are made by annealing GaN NWs with a thick radial shell, reforming them into hexagonal flat‐top prisms with six equivalents either m‐ or s‐facets depending on the initial heights of the top pyramid and m‐facets of the NWs. This shape is kinetically controlled and the reformation can be explained with a phenomenological model based on Wulff construction that have been developed. It is expected that the results will inspire further research into micron‐sized III‐nitride‐based devices. Abstract : Dislocation‐free and atomically smooth 3D GaN microprisms are realized via two key epitaxial steps: growth from masked holes to eliminate threading dislocations from the substrate, followed by a crucial reformation step to achieve prisms with six parallel and equivalent side facets, with a micrometer‐sized top surface. The image shows 30° tilted‐view and side‐view SEM images of the GaN microprisms.